PENGARUH KUALITAS PRODUK, HARGA DAN INFLUENCER MARKETING TERHADAP KEPUTUSAN PEMBELIAN SCARLETT BODY WHITENING - Cindy Septia Pratiwi; Agus Purnomo Sidi (STIE Mandala Jember, 2022)
This research aimed to figure out the influence between product quality, price and marketing influencer with the purchasing decision of Scarlett Body Whitening in East Java. The research instrument employed questionnaire to collect data from Scarlett Body Whitening consumers in East Java. Since there was no valid data for number of the consumers, the research used Roscoe method to take the sample. Data analyzed using multiple linear regression test. Product quality and price have a positive and significant effect on purchasing decisions. Meanwhile, the marketing influencer had no significant effect on purchase decision for Scarlett Body Whitening. Need further research to ensure that marketing influencer had an effect on purchase decision. Keywords: Product quality, price, marketing influencer, buying decision